STUDY OF GOOD CAUSE PURCHASE IN INDONESIA - Gumulya, Devanny (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2022)
Nowadays, consumers are more aware and interested in products that have a good cause, such as charity, fair trade with employees and partners, and are environmentally friendly. The study focuses on linking the literature review on green product purchase intention with the big data taken from a survey conducted by the Indonesian private survey firm, Jakpat, in 2017. The survey results reflect the views of 1,114 Indonesian consumers on good cause purchase. The demographics of the respondents are nationwide. Most of them are Muslim working-class men aged 20–25 years old and hold high school and bachelor's degrees. Respondents mostly come from major cities such as DKI Jakarta, West Java, Central Java, and East Java. The study results revealed that the perceived benefits of green products to Indonesian consumers are safe ingredients, a safe manufacturing process, and a sense that they support fair trade practices. Second, Indonesian consumers support good causes such as education and health care for the poor, reducing hunger and poverty, and donating to disaster relief. Third, Indonesian consumers are willing to pay more for organic food and personal care products. Fourth, Indonesian consumers are concerned about the manufacturing and production of green products, as well as the well-being of those who make them. Finally, the study makes several recommendations for sustainable entrepreneurs in terms of good cause marketing content strategy. This study adds to the existing body of knowledge about green product purchasing intentions.